Undergraduate Students’ Intrinsic Motivation and Learning Outcome in General Genetics (BTC 214) Using Technology-Mediated Synchronous and Asynchronous Learning Approaches - Penda, Bibiana Mwuese; Ajayi, Victor Oluwatosin; Audu, Christina Tanko (Innovare Journal of Education, 2026)
This study investigates how technology-mediated learning, specifically synchronous (real-time) and asynchronous (self-paced) approaches, impacts undergraduate students’ intrinsic motivation and <a href="https://www.google.com/search?cs=1&sca_esv=a468913120da2fdd&sxsrf=AE3TifNN6aDCZ_FH-EERiJAR_bjt-DVlQA%3A1760788118595&q=learning+outcomes&sa=X&ved=2ahUKEwj5upTy1q2QAxWhW0EAHR2YAaIQxccNegQIERAB&mstk=AUtExfBowweAfMjSSpn5o572li1uD3MNVFM2Dz8pV9upPOQPXBN8mtO6qtjQKrrnxgX2BB7J15U-la6DmvBA-sbgqZL67w8mcBcTPzEv9pET26Z_bjRdoyFmCQvDvn-_aeaw9ONRipwDCAjLPUQyVqBob9t2VsWWQehjMJeOXBPiz_pPDjg&csui=3">learning outcomes in a general genetics course (BTC 214). The research design adopted in this study is a quasi-experimental, non-randomized, pre-test/post-test, control-group design. The Intrinsic Motivation Scale (IMS) and General Genetics Learning Outcome Test (GGLOT) are the instruments used for data collection. IMS and GGLOT were validated and trial-tested, yielding reliability values of 0.89 and 0.94, respectively, using Cronbach’s alpha and the Kuder-Richardson (KR-21) formula. This quasi-experimental study employed a convenience sample of intact class groups, comprising all 137 undergraduate students enrolled in Biology and Biology Education (200 level) at Federal University Lokoja, Nigeria during the 2024/2025 session. Four research questions and four null hypotheses guided the study. The research questions were answered using M and SD scores, and the null hypotheses were tested using analysis of covariance. It was established among others that there was a significant difference in the mean intrinsic motivation ratings and learning outcome scores of undergraduate students taught general genetics using synchronous learning approach (SLA), asynchronous learning approach (ALA), and modified lecture method (MLM) F(2, 130) = 95.06, p < .05 and F(2, 130) = 164.00, p < .05 respectively. It was recommended that lecturers be encouraged to use technology-mediated pedagogies (TMPs), such as SLA and ALA, to elevate undergraduate students’ intrinsic motivation and learning outcomes in general genetics.